EH Domain-Containing 2 Deficiency Restricts Adipose Tissue Expansion and Impairs Lipolysis in Primary Inguinal Adipocytes - Fryklund, Claes; Morén, Björn; Shah, Shrenika; Grossi, Mario; Degerman, Eva; Matthaeus, Claudia; Stenkula, Karin G. (Frontiers in Physiology, 2021)
Lipid uptake can be facilitated via caveolae, specific plasma membrane invaginations abundantly expressed in adipocytes. The dynamin-related protein EH domain-containing 2 (EHD2) stabilizes caveolae at the cell surface. Here, we have examined the importance of EHD2 for lipid handling using primary adipocytes isolated from EHD2 knockout (Ehd2-/-) C57BL6/N mice. Following high-fat diet feeding, we found a clear impairment of epididymal, but not inguinal, adipose tissue expansion in Ehd2-/- compared with Ehd2+/+ (WT) mice. Cell size distribution analysis revealed that Ehd2-/- mice had a lower proportion of small adipocytes, and an accumulation of medium-sized adipocytes in both epididymal and inguinal adipose tissue. Further, PPARγ activity, FABP4 and caveolin-1 expression were decreased in adipocytes isolated from Ehd2-/- mice. Inguinal adipocytes isolated from Ehd2-/- mice displayed reduced lipolysis in response to beta adrenergic receptor agonist, which was associated with reduced phosphorylation of perilipin-1 and hormone sensitive lipase. This impairment could not be rescued using a cAMP analogue, indicating that impaired lipolysis in Ehd2-/- primary adipocytes likely occurs at the level of, or downstream of, PKA. Altogether, these findings pinpoint the importance of EHD2 for maintained intracellular lipid metabolism, and emphasize differences in mechanisms regulating lipid handling in various adipose-tissue depots.